INTERNATIONALIZATION OF ENTREPRENEURSHIP AND THE COMPETITIVENESS CAPACITY OF REGIONS: Array - Babayev, V.; Sukhonos, M.; Dymchenko, O.; Rudachenko, O.; Tararuiev, Y. (Municipal economy of cities. Series: «Economy science», 2020)
The article identifies the potential of regions competitiveness, taking into account their relationship with specialization and place in the territorial division of labor. It is proved that the region should pursue a competitive policy in the field of economic, organizational, production and technological, business, image and other development tasks. The competitiveness of regions among themselves and in international markets creates an integral, synergistic effect of state economic policy, and therefore the state in various ways supports the development of the competitive potential of each of its regions. For Ukraine, the problem of assessing the competitiveness of regions is particularly relevant, which is especially felt in the context of trends in decentralization. The development of rational and scientifically sound recommendations for determining the competitiveness of the regions of Ukraine requires comprehensive consideration of foreign and domestic experience in this area, so it is advisable to consider modern methods developed to solve this problem. The authors determine the regularity of a fairly close relationship between the level of competitiveness of the region with a set of indicators of socio-economic potential of the region and grouped the latter into 10 integrated indicators. According to the ranking priority of the Kharkiv region, its potential for competitiveness is at a high level and is able to provide the region with high rates of economic growth. Taking into account the ranking positions of the regions in terms of 10 indicators. The proposed method of calculating the competitiveness indices of regions, according to the authors, is relevant and accessible from the standpoint of obtaining initial data, as evidenced by the use as data sources for calculations of modern statistical and other publications, information from which is freely available. Thus, the location of the regions on the ranking scale of selected indicators can be determined by the fact that in regional development there are significant disparities and differences. However, more than half of the regions have their advantages on individual indicators. The study has identified these benefits and each region can use this in its development strategy and in developing measures to increase competitiveness.